2015
DOI: 10.1007/s10658-015-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and recombination analysis of an Indian isolate of Onion yellow dwarf virus

Abstract: This study presents the first whole genome sequence of Onion yellow dwarf virus (OYDV isolate RR1) from onion (Allium cepa) in India along with phylogenetic and recombination studies. We examined the sequence variability, distribution of simple sequence repeats (SSRs), and recombination breakpoints of different OYDV geographical isolates. The P1 and P3 regions of OYDV show a higher rate of sequence variability in amino acid and nucleotide sequences than other genomic regions. Entropy peaks of deduced amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Incidence of mixed infections with different begomoviruses and satellite molecules as well as the emergence of the new variants of viruses due to recombination of existing ones ( Fiallo-Olivé et al, 2019 ), has manifested the adaptability to new hosts, which has posed such a serious threat to many economically important crops ( Varma and Malathi, 2003 ). Recombination is a vital evolutionary approach for viruses ( Pagán and García-Arenal, 2018 ; Zaffalon et al, 2012 ) to get adapted to new environmental conditions ( Verma et al, 2015 ) concomitantly, it is the major driving force in the evolution of many viruses and also has been adequately revealed for ssDNA viruses especially begomoviruses ( Martin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of mixed infections with different begomoviruses and satellite molecules as well as the emergence of the new variants of viruses due to recombination of existing ones ( Fiallo-Olivé et al, 2019 ), has manifested the adaptability to new hosts, which has posed such a serious threat to many economically important crops ( Varma and Malathi, 2003 ). Recombination is a vital evolutionary approach for viruses ( Pagán and García-Arenal, 2018 ; Zaffalon et al, 2012 ) to get adapted to new environmental conditions ( Verma et al, 2015 ) concomitantly, it is the major driving force in the evolution of many viruses and also has been adequately revealed for ssDNA viruses especially begomoviruses ( Martin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…High sequence homology was also reported between OYDV isolates from India and those from Australia, i.e. 98% (Verma et al 2015). Similarly, Baghalian et al (2010) reported that among OYDV isolates from Iran shared 79 to 99% homology of the nucleotide sequence of coat protein gene, while with OYDV isolates from other countries Iran isolates shared 79 to 98% identity.…”
Section: Amplification Of Oydv and Sequence Analysismentioning
confidence: 74%
“…Onion and garlic are affected with more than 20 notorious viruses of different genera including Allexivirus, Potyvirus, Tospovirus and Carlavirus are detected worldwide (Verma et al, 2015;Mansouri et al, 2021a). Symptoms produced by these viruses are identical to various other diseases and abiotic stresses, so difficult to identify based on symptoms only.…”
Section: Discussionmentioning
confidence: 99%